Antagonism of quercetin against tremor induced by unilateral striatal lesion of 6-OHDA in rats. Issue 1 (2nd January 2016) - Mu, Xin; Yuan, Xia; Du, Li-Da; He, Guo-Rong; Du, Guan-Hua
Abstract : Quercetin, a flavonoid present in many plants, is reported to be effective in models of neurodegenerative diseases. The aim of the present study was to evaluate the anti-tremor effects of quercetin in 6-hydroxydopamine (6-OHDA)-induced rat model of Parkinson's disease. In rats, quercetin had no effect on apomorphine-induced rotations, but it could significantly attenuate muscle tremor of 6-OHDA lesioned rats. Interestingly, quercetin could decrease the burst frequency in a dose- and time-dependent manner. These results suggest that quercetin may have a protective effect on models to mimic muscle tremors of Parkinson's disease. This effect of quercetin may be associated with serotonergic system, but further study is needed.